2013 International Conference on Electronics, Computer and Computation (ICECCO) 2013
DOI: 10.1109/icecco.2013.6718278
|View full text |Cite
|
Sign up to set email alerts
|

Design and PID control of two wheeled autonomous balance robot

Abstract: In this study, a two-wheeled autonomous balance robot has been designed and implemented practically. A visual computer interface based on Qt-Creator has been created. Thanks to the computer interface, different control algorithms can be performed on the robot easily, control parameters can be set up online, filter algorithms in various structures can be tried and the reaction of these changeable values to the system can be observed. The effects of some controllers such as Proportional (P), Proportional-Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The only drawback of this controller is large overshoot. Unluturk Ali et al [15] observed the effects of P, PI and PID controllers on selfbalancing robot with the help of visual computer interface based on Qt-creator [16]. They observed that P-controller, alone is not sufficient for robot's balance.…”
Section: Introductionmentioning
confidence: 99%
“…The only drawback of this controller is large overshoot. Unluturk Ali et al [15] observed the effects of P, PI and PID controllers on selfbalancing robot with the help of visual computer interface based on Qt-creator [16]. They observed that P-controller, alone is not sufficient for robot's balance.…”
Section: Introductionmentioning
confidence: 99%
“…The only drawback of this controller is large overshoot. Unluturk Ali et al 15 observed the effects of P, PI and PID controllers on self-balancing robot with the help of visual computer interface based on Qt-creator 16 . They observed that P-controller, alone is not sufficient for robot's balance.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, self-balancing systems have attracted increased attention, since engineers and researchers are now able to test control algorithms on the inherent non-linear behaviour of such systems. Previous studies deploying basic Proportional Integral Derivative (PID) controllers have been tested [1–3]. However, the addition of motion control of a supporting moving platform requires a more sophisticated control scheme, such as a cascade PID.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies deploying basic Proportional Integral Derivative (PID) controllers have been tested [1][2][3]. However, the addition of motion control of a supporting moving platform requires a more sophisticated control scheme, such as a cascade PID.…”
Section: Introductionmentioning
confidence: 99%